Influence of Extracurricular Services on Students’ Academic Achievement in Secondary Schools in Kwara State: A Qualitative Approach - Yusuf Suleiman; Zahyah Bt Hanaf; Muhajir Tanslikhan (Universitas Muhammadiyah Surakarta, 2019)
Extracurricular services are regarded as essential services in school system. Studies suggest that access to the services lead to students’ academic success. Literature shows that the use of qualitative approach to investigate extracurricular services is limited. In view of the foregoing, this study examined the perceived influence of extracurricular services on students’ academic achievement in secondary schools. Twenty (20) principals were selected from the three senatorial districts of Kwara State using stratified, purposive and convenience sampling techniques. Instruments used include interview and observation methods to collect relevant data from the participants. Specifically, observation method was used to complement findings from interview. Our findings reveal that extracurricular services influenced students’ academic achievement. Our findings revealed also that inadequate availability of extracurricular facilities and personnel are the factors militating against effective provision of extracurricular services. This study recommends that adequate extracurricular facilities (football pitch, volleyball court, hall for social activities, etc.) should be available in schools. Lastly, adequate extracurricular services personnel should be deployed to schools to ensure active participation of students in various activities.